In Situ Carbon Coated LiNi0.5Mn1.5O4 Cathode Material Prepared by Prepolymer of Melamine Formaldehyde Resin Assisted Method - Wei Yang; Haifeng Dang; Shengzhou Chen; Hanbo Zou; Zili Liu; Jing Lin; Weiming Lin (International Journal of Polymer Science)
Carbon coated spinel LiNi0.5Mn1.5O4 were prepared by spray-drying using prepolymer of melamine formaldehyde resin (PMF) as carbon source of carbon coating layer. The PMF carbon coated LiNi0.5Mn1.5O4 was characterized by XRD, SEM, and other electrochemical measurements. The as-prepared lithium nickel manganese oxide has the cubic face-centered spinel structure with a space group of Fd3m. It showed good electrochemical performance as a cathode material for lithium ion battery. After 100 discharge and charge cycles at 0.5 C rate, the specific discharge capacity of carbon coated LiNi0.5Mn1.5O4 was 130 mAh·g−1, and the corresponding capacity retention was 98.8%. The 100th cycle specific discharge capacity at 10 C rate of carbon coated LiNi0.5Mn1.5O4 was 105.4 mAh·g−1, and even the corresponding capacity retention was 95.2%.